2016
DOI: 10.1371/journal.pone.0168682
|View full text |Cite
|
Sign up to set email alerts
|

Albuminuria Is Associated with Open-Angle Glaucoma in Nondiabetic Korean Subjects: A Cross-Sectional Study

Abstract: ObjectiveSystemic vascular dysfunction has been suggested to contribute to glaucomatous damage. Albuminuria is a surrogate marker of endothelial injury, including vessels. However, their relationship is not well understood. This study aimed to investigate the association between albuminuria and the prevalence of open-angle glaucoma (OAG) in nondiabetic subjects.MethodsWe conducted a cross-sectional study of 4186 nondiabetic participants aged 19 years or older from the 2011–2012 Korea National Health and Nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…12 Another previous study also using the KNHANES 2011 to 2012 reported that albuminuria, even low-grade, was significantly associated with OAG in nondiabetic subjects. 26 These results are concordant with the main findings of our study that CRD increased the risk of following glaucoma development in the Korean population, although our study was a longitudinal study compared with the cross-sectional previous studies. Another populationbased study using the Taiwan Longitudinal Health Insurance Database 2000, they found that chronic renal failure (CRF) had a significantly higher prevalence of glaucoma and other eye diseases, including retinal disorders, uveitis, and cataract, compared with patients without CRF.…”
Section: Discussionsupporting
confidence: 93%
“…12 Another previous study also using the KNHANES 2011 to 2012 reported that albuminuria, even low-grade, was significantly associated with OAG in nondiabetic subjects. 26 These results are concordant with the main findings of our study that CRD increased the risk of following glaucoma development in the Korean population, although our study was a longitudinal study compared with the cross-sectional previous studies. Another populationbased study using the Taiwan Longitudinal Health Insurance Database 2000, they found that chronic renal failure (CRF) had a significantly higher prevalence of glaucoma and other eye diseases, including retinal disorders, uveitis, and cataract, compared with patients without CRF.…”
Section: Discussionsupporting
confidence: 93%
“…Another interesting finding is that higher UACR was independently associated with increased GCC-FLV and GCC-GLV. Previous studies have documented that albuminuria was independently associated with POAG ( Kim et al, 2016 ), an ocular disease characterized by loss of the retinal ganglion cells in the retina ( Shin et al, 2018 ), suggesting that albuminuria might be associated with retinal ganglion cell loss. In this regard, albuminuria (as indicated by higher UACR) might be a potential biomarker suggestive of neuronal damage in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…CHO, cholesterol; CI, confidence interval; LDL-C, low density lipoprotein cholesterol; HDL-C, high density lipoprotein cholesterol; OR, odds ratio; POAG, primary open angle glaucoma; NS, non-significant; NTG, normal tension glaucoma. In ( 107 ) and ( 110 ), age was significantly different between controls and cases.…”
Section: Cholesterol Oxysterols and Glaucomamentioning
confidence: 86%
“… Results are given as mean ± SD (except for ( 110 ) mean ± SE) or OR, 95%CI. See references for details regarding specific statistical methods.…”
Section: Cholesterol Oxysterols and Glaucomamentioning
confidence: 99%